POROSITY-TO-CEMENT INDEX CONTROLLING UNCONFINED COMPRESSIVE STRENGTH OF A CEMENTED SOIL - Jair Arrieta; Carlos Millan; Fernando Jove (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The present work presents the development of equations that estimate the simple compressive strength (qu) of silty soil in Curitiba, Brazil, stabilized with Portland cement type V (CP V). The equations were developed using the porosity/volumetric cement content ratio (?/Civ) or voids/cement ratio. Soil-cement specimens were molded in four apparent dry specific weights (?d) using cement contents of 3%, 5%, 7%, and 9% (concerning the dry weight of the soil) and subsequently tested under saturated conditions after of 28 days of cure. The results show that the addition of cement increases the strength of soil-cement mixtures linearly. Increasing the dry mold density also increases the qu values. On the other hand, if the porosity of the mixtures decreases, qu increases. It is shown that with the decrease of the ?/Civ ratio the values of qu increase. The maximum qu value obtained with Portland V cement was 3365.1 kPa. A general estimation equation for q was developed to estimate the strength of mixtures. The equations and mathematical adjustments demonstrate that it is possible to estimate the qu value of the stabilized soil within the ranges of ?d, amount of cement, ?/Civ ratio, and curing time used in the present work.